Mortalidade por infarto agudo do miocárdio no estado do Espírito Santo de 1999 a 2012: uma análise de tendência (Brazilian Journal of Health Research, 2019)
Mortality rates due to acute myocardial infarction recorded in Espírito Santo state, from 1999 to 2012: a trend analysis